Effects of dietary nitrogen and/or phosphorus reduction on mineral homeostasis and regulatory mechanisms in young goats - Zillinger, Luisa S.; Hustedt, Karin; Schnepel, Nadine; Hirche, Frank; Schmicke, Marion; Stangl, Gabriele I.; Muscher-Banse, Alexandra S. (Frontiers in Veterinary Science, 2024)
The reduction of nitrogen (N) and phosphorus (P) in ruminant feed is desirable due to costs and negative environmental impact. Ruminants are able to utilize N and P through endogenous recycling, particularly in times of scarcity. When N and/or P were reduced, changes in mineral homeostasis associated with modulation of renal calcitriol metabolism occurred. The aim of this study was to investigate the potential effects of dietary N-and/or Preduction on the regulatory mechanisms of mineral transport in the kidney and its hormonal regulation in young goats. During N-reduction, calcium (Ca) and magnesium (Mg) concentrations in blood decreased, accompanied by a lower protein expression of cytochrome P450 family 27 subfamily B member 1 (CYP27B1) (P = 0.016). The P-reduced fed goats had low blood phosphate concentrations with simultaneously high Ca and Mg levels. The insulinlike growth factor 1 concentrations decreased significantly with P-reduction. Furthermore, gene expression of CYP27B1 (P < 0.001) and both gene (P = 0.025) and protein (P = 0.016) expression of the fibroblast growth factor receptor 1c isoform in the kidney were also significantly reduced during a P-reduced diet. ERK1/2 activation exhibited a trend towards reduction in P-reduced animals. Interestingly, calcitriol concentrations remained unaffected by either restriction individually, but interacted significantly with N and P (P = 0.014). Additionally, fibroblast growth factor 23 mRNA expression in bone decreased significantly with P-restriction (P < 0.001). These results shed light on the complex metabolic and regulatory responses of mineral transport of young goats to dietary N and P restriction.